Social Justice Theory and Practice for Social Work Critical and Philosophical Perspectives - Watts, Lynelle; Hodgson, David; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book offers a much-needed critical overview of the concept of social justice and its application in professional social work practice. Social justice has a rich conceptual genealogy in critical theory and political philosophy. For students, teachers and social workers concerned with empowerment, social change and human rights, this book provides a guide to the key ideas and thinkers, crucial historical developments and contemporary debates about social justice. It synthesises interdisciplinary knowledge and offers a new framework for practice, including a clear and practical exposition of four domains of skills and knowledge important for social justice informed social work. The book also contributes to social work pedagogy by offering a comprehensive set of learning outcomes that can be used to design curriculum, teaching and learning, and further research into social justice praxis. This book provides a range of philosophical and critical perspectives to support and inform social work professional knowledge and skills. In its tight knitting together of theory and practice this book links philosophical and moral principles with an understanding of how to engage with social justice in a way that is relevant to social work.
Chapter 1. Injustice and its many forms -- Chapter 2. Social justice as an ethic of social work -- Chapter 3. A critical history of the social work response to social justice -- Chapter 4. Capitalism and neoliberalism -- Chapter 5. Power and knowledge -- Chapter 6. Critical social science and critical theory -- Chapter 7. Distributive theories of justice -- Chapter 8. Democracy and participation -- Chapter 9. Human rights and autonomy -- Chapter 10. Social justice and social work practice -- Chapter 11. Social justice and social work education.
Keywords: Social service; Human rights; Political science -- Philosophy; Family policy; Social Work; Human Rights; Political Philosophy; Children, Youth and Family Policy